Evaluasi Lanjut Penyebaran Lalat Argentina sebagai Pengendali Gulma Siam - Tri Harjaka; Soeprapto Mangoendihardjo (Jurnal Perlindungan Tanaman Indonesia, 2010)
The stem-galling fly, Cecidochares connexa is one of the natural enemies introduced into Indonesia for the control Siam weed (Chromolaena odorata). The research investigated to know the spread and establisment of C. connexa in Central Java and East Java. Survey was done in six districts started from Gunung Kidul until Madiun for sampling of Siam weed stems and calculate the parasitations of C. connexa. The results showed that C. connexa as natural enemies of Siam weed has established in Central Java and East Java with parasitation of stem reached 54.33%. C. connexa have spread more than 200 km from first site-released location in Wanagama I, Yogyakarta.